Study of Aldosterone Synthase Inhibition as an Add‐On Therapy in Resistant Hypertension. Issue 3 (14th December 2012) - Karns, Adam D.; Bral, Jacqueline M.; Hartman, Daniel; Peppard, Thomas; Schumacher, Christoph
<x xml:space="preserve">Abstract</x> Aldosterone inhibition with mineralcorticoid receptor antagonists (MRAs) is an effective treatment for resistant hypertension. Aldosterone synthase inhibitors (ASIs) are currently being investigated as a new therapeutic strategy to reduce aldosterone secretion from the adrenal gland. In this study, the efficacy and safety of the first‐generation ASI LCI699 (0.25 mg twice daily, 1 mg 4 once daily, and 0.5 mg/1 mg twice daily) was compared with placebo and eplerenone (50 mg twice daily), in patients with resistant hypertension. Placebo‐adjusted decreases in systolic blood pressure (BP) with LCI699 ranged from 2.6 mm Hg to 4.3 mm Hg at week 8; changes in diastolic BP ranged from +0.3 mm Hg to −1.2 mm Hg. However, reductions were smaller than observed with eplerenone 50 mg twice daily (9.9 mm Hg and 2.9 mm Hg for systolic and diastolic BP, respectively) and not statistically significant vs placebo. LCI699 suppressed plasma aldosterone levels in a dose‐related manner with corresponding dose‐dependent increases in plasma renin activity and plasma 11‐deoxycorticosterone. LCI699 and eplerenone were well tolerated. These data demonstrate that aldosterone synthesis inhibition with LCI699 lowers BP modestly in patients with resistant hypertension. Aldosterone synthesis inhibition might offer an attractive adjunct to aldosterone receptor blockade, although the potential of a combination MRA/ASI has not yet been tested. J Clin Hypertens (Greenwich). 2012;00:00–00. ©2012 Wiley Periodicals, Inc.